Respuesta :

Answer:

[tex]p =2.5[/tex]

[tex]q = 0.5[/tex]

Step-by-step explanation:

Given

[tex]2x + 3y = 7[/tex]

[tex]( p-q ) x + (p+q) y = 3 p + q -2[/tex]

Required

Find p and q

To do this, we make direct comparison between the given expressions.

[tex]2x + 3y = 7[/tex] and [tex]( p-q ) x + (p+q) y = 3 p + q -2[/tex]

This implies that:

[tex](p - q)x = 2x[/tex]

[tex](p+q)y = 3y[/tex]

[tex]3(p + q) - 2 = 7[/tex]

So, we have:

[tex]p - q = 2[/tex] --- (1)

[tex]p+q =3[/tex] -- (2)

[tex]3(p + q) - 2 = 7[/tex] --- (3)

If [tex](1)\ and\ (2)[/tex] are true, then [tex](3)\ must[/tex] be true.

So, we only solve [tex](1)\ and\ (2)[/tex]

Add (1) and (2) to eliminate q

[tex]p+p-q+q=2+3[/tex]

[tex]2p=5[/tex]

Solve for p

[tex]p = 5/2[/tex]

[tex]p =2.5[/tex]

Substitute [tex]p =2.5[/tex] in (2)

[tex]p+q =3[/tex]

[tex]q = 3 - p[/tex]

[tex]q = 3 - 2.5[/tex]

[tex]q = 0.5[/tex]